Using DeepSeek LLM AI System on Database Concepts and Design - Pornphol, Putsadee; Chittayasothorn, Suphamit (My University, 2025)
The use of Large Language Model (LLM) artificial intelligence (AI) systems in learning environments is ubiquitous. They are used by learners for self-studying, assignments, and exam preparation. Practitioners use them as junior assistants. Major concerns include the correctness and the completeness of the answers generated by the AI systems. In this paper, we explore how well an LLM AI system DeepSeek, answers database concepts and design questions. Selected questions on database design and frequently misunderstood topics are asked. Related knowledge is explained. The answers are reviewed and marked to provide an assessment on its use in the subject area.
Keywords: Database Design; DeepSeek; ER Model; LLM AI; Relational Database